2005
DOI: 10.1542/peds.2004-0905
|View full text |Cite
|
Sign up to set email alerts
|

New and Lingering Controversies in Pediatric End-of-Life Care

Abstract: There is a need for more hospital-based ethics education and more interdisciplinary and cross-subspecialty discussion of inherently complex and stressful pediatric end-of-life cases. Education should focus on establishing appropriate goals of care, as well as on pain management, medically supplied nutrition and hydration, and the appropriate use of paralytic agents. More research is needed on clinicians' regard for the dead-donor rule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
0
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(144 citation statements)
references
References 21 publications
4
128
0
8
Order By: Relevance
“…This experience is consistent with recent published data from a medical intensive care unit where nurses were far more likely to experience moral distress in situations of what they felt was 'over-aggressive' care rather than situations of undertreatment. 16 A recent study in a pediatric context 17 also found that about 20 times as many nurses, 15 times as many house officers and 10 times as many attending physicians agreed with the statement, 'Sometimes I feel we are saving children who should not be saved,' as agreed with the statement, 'Sometimes I feel we give up on children too soon'. However, if a respondent had frequent ethical concerns about failure to treat an infant in the NICU, they may not have responded that they had frequent confrontation.…”
Section: Resultsmentioning
confidence: 96%
“…This experience is consistent with recent published data from a medical intensive care unit where nurses were far more likely to experience moral distress in situations of what they felt was 'over-aggressive' care rather than situations of undertreatment. 16 A recent study in a pediatric context 17 also found that about 20 times as many nurses, 15 times as many house officers and 10 times as many attending physicians agreed with the statement, 'Sometimes I feel we are saving children who should not be saved,' as agreed with the statement, 'Sometimes I feel we give up on children too soon'. However, if a respondent had frequent ethical concerns about failure to treat an infant in the NICU, they may not have responded that they had frequent confrontation.…”
Section: Resultsmentioning
confidence: 96%
“…This process of community consultation, combined with attending to core characteristics of successful interventions, yielded remarkably high rates of retention, overcoming previously noted barriers to palliative care research. 37 FACE demonstrated feasibility, enrolling the targeted sample size and yielding a high rate of satisfaction for African American families, who generally have been underrepresented in EOL research (NIH State of the Science Conference Statement on Improving End-of-Life Care, December [6][7][8]2004). The adaptation of the sessions to be culturally sensitive through a process of community review [38][39][40][41][42][43] was successful.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Despite these recommendations and reports, in practice, goals for shared decision-making with adolescents often fail. [5][6][7] There is no existing model that includes adolescents in discussions about their EOL care and recognizes their capacity to provide informed consent=assent for medical treatment. 8 Acceptability and feasibility of such a program will be greater when it is informed by a research base that includes the intended consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Higher rates of agreement were found in two surveys of PICU physicians in which about threequarters of respondents agreed that non-initiating is ethically the same as withdrawing a treatment. 10,11 A study of ten European countries' neonatologists showed only about one-third to one-half agreed that withdrawing and withholding treatment are ethically equivalent. 14 Which action neonatologists regard as more ethically or emotionally challenging is not clear by the responses, and deserves further study.…”
Section: Withholding Of Lsts Across Scenariosmentioning
confidence: 99%
“…[7][8][9] Several studies explore physicians' end-of-life (EOL) decision-making in pediatric intensive care units and in adult critical care settings. [10][11][12] However, an extensive review of the literature finds no similar studies of US neonatologists and finds only a few EOL surveys of neonatology outside the US. Little is known about neonatologists' views on limiting care outside of the delivery room, as most research focuses on managing the extremely premature or severely affected infant immediately after birth.…”
Section: Introductionmentioning
confidence: 99%